2021
DOI: 10.1158/1078-0432.ccr-20-4391
|View full text |Cite
|
Sign up to set email alerts
|

Abiraterone Acetate Induces CREB1 Phosphorylation and Enhances the Function of the CBP-p300 Complex, Leading to Resistance in Prostate Cancer Cells

Abstract: Purpose: Abiraterone acetate (AA), an inhibitor of CYP17A1, is an FDA-approved drug for advanced prostate cancer. However, not all patients respond to AA, and AA resistance ultimately develops in patients who initially respond. We aimed to identify AA resistance mechanisms in prostate cancer cells. Experimental Design:We established several AA-resistant cell lines and performed a comprehensive study on mechanisms involved in AA resistance development. RNA-seq and phospho-kinase array screenings were performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…The detailed results are provided in SI Appendix , Table S2 . Interestingly, a collection of the genes that are implicated in these signaling pathways, including WNT4 ( 49 ), LRP5 ( 50 ), BRAF ( 51 ), GNA13 ( 52 ), PDPK1 ( 53 ), SPHK1 ( 54 ), PRKCA ( 55 ), and CREB1 ( 56 ), have well-recognized roles in drug resistance. Further genomic profiling of the components of the BRD4/LSD1/NuRD complex showed a significant enrichment of these components at the locus of WNT4 , PDPK1 , LRP5 , and GNA13 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed results are provided in SI Appendix , Table S2 . Interestingly, a collection of the genes that are implicated in these signaling pathways, including WNT4 ( 49 ), LRP5 ( 50 ), BRAF ( 51 ), GNA13 ( 52 ), PDPK1 ( 53 ), SPHK1 ( 54 ), PRKCA ( 55 ), and CREB1 ( 56 ), have well-recognized roles in drug resistance. Further genomic profiling of the components of the BRD4/LSD1/NuRD complex showed a significant enrichment of these components at the locus of WNT4 , PDPK1 , LRP5 , and GNA13 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the BRD4/LSD1/NuRD complex–mediated restriction of super-enhancer activation influences various genes, including WNT4 , LRP5 , BRAF , GNA13 , PDPK1 , SPHK1 , PRKCA , and CREB1 , and impacts several cellular signaling pathways including the PI3K-AKT and WNT pathways. Although these genes have been documented to play important roles in drug resistance ( 49 56 ), the PI3K-AKT and WNT pathways are important cellular signaling mechanisms profoundly affecting biological activities such as cell growth and differentiation, transcription, replication, apoptosis, and aging ( 78 , 79 ). It will be interesting in future studies to investigate the regulation of these cellular processes by the BRD4/LSD1/NuRD complex and the biological readouts stemmed from the BRD4/LSD1/NuRD complex–mediated restriction of super-enhancer activation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al proposed a mechanism of EP300 downregulation by miR-106b∼25, which increased tolerance to doxorubicin and helped to avoid doxorubicin-induced senescence in breast cancer cells [ 42 ]. In turn, increased activity of EP300 correlated with enhanced resistance to a variety of compounds in prostate cancer [ 43 , 44 , 45 ]. In breast cancer cells, inhibition of acetyltransferase sensitized cancer cells to a variety of chemotherapeutics, by impeding drug efflux and increasing drug accumulation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer cells, phosphorylation of CREB1 was induced by norepinephrine to facilitate cell proliferation, migration, and invasion [ 45 ]. Besides, in prostate cancer cells, abiraterone acetate treatment can induce CREB1 phosphorylation, which in turn enhances CBP/p300 activity and lead to alterations in global gene expression and subsequently drug resistance [ 46 ]. Moreover, studies have demonstrated an indispensable role of CREB1 in lipid synthesis in liver and adipose in nonruminants.…”
Section: Discussionmentioning
confidence: 99%